Diastolic flow in the left ventricular outflow tract – A normal physiological and underappreciated echocardiographic finding. Issue 3 (27th June 2022) - Cowie, Brian; Costello, Ben; Wright, Leah; Janssens, Kristel; Howden, Erin; Flannery, Darragh; Foulkes, Steve; Kluger, Roman; Gerche, Andre La
Abstract: Purpose: Diastolic waveforms in the left ventricular outflow tract (LVOT) are commonly observed with Doppler echocardiography. The incidence and mechanism are not well described. Methods: This was a retrospective observational study of 186 adult patients, athletes and non‐athletes, free of known cardiac disease, presenting for comprehensive transthoracic echocardiography at a research institute. We aimed to evaluate the incidence and echocardiographic associations between LVOT diastolic waveforms. Results: Left ventricular outflow tract early to mid‐diastolic waveforms were present in 100% of athletes and 95% of non‐athletes. The LVOT diastolic velocity time integral was larger in athletes than non‐athletes with a mean 8.3 cm (95% CI (7.6–8.9)) vs. 5.1 cm (4.4–5.9) (P < 0.0001). Multivariate predictors of this diastolic waveform were age (P = 0.002), slower heart rate (P = 0.035), higher stroke volume (P = 0.003), large mitral E (P = 0.019) and higher E/e' (P = 0.015). Discussion: An LVOT early diastolic wave is a normal physiological finding. It is related to a flow vortex redirecting diastolic mitral inflow around anterior mitral valve leaflet into the LVOT. Conclusions: Early to mid‐diastolic LVOT waves are present in almost all patients but more prominent in young athletes than non‐athletes. Diastolic LVOT waves increase with younger age, slower heart rate, larger stroke volume and enhanced diastolic function.